Prevalence and diagnosis of temporomandibular dysfunction in outpatient adults clinical practice at General Hospital Maria Auxiliadora - Benites-Vega, Juan Carlos (2021)
The objective of this study was to determine the diagnosis and prevalence of temporomandibular joint dysfunction (TMJD) in Maria Auxiliadora General Hospital in Lima, Peru, during 2019. Material and Methods: This is a prospective randomized longitudinal descriptive study. The sample included 76 patients, and Research Criteria for Diagnosing Temporomandibular Joint Disorders were used. Results: We found that 73.7% patients were female, particularly belonging to the 30-39 years age group (35.6%). TMJD etiology is multifactorial and it is related to structural, functional, and psychological factors. When diagnosing TMJD, headache was the main symptom (38.1%), and pain on palpation (51.4%) was the most prominent sign on clinical examination, particularly in females (38.2%). Mixed anxiety-depressive disorder, was the most frequent mental status alteration associated with TMJD found on clinical examination (50.0%), and it also was more frequently found in females (38.2%). A combination of general clinical and ear, nose, and throat examination allowed reaching a diagnosis in 77.6% of all subjects. Conclusion: Patients with TMJD who present with headache and concomitantly with anxiety-depression, require integrative and early therapy management, so they may be reinstalled to their working environment and improve their productivity. TMJD should be considered as a frequent cause of headache.